Structural Breaks, Stability and Demand for Money in South Africa - Malumisa, Sambulo (Journal of Economics and Behavioral Studies, 2015)
The paper tests the null hypothesis of a stable long-run money demand in South Africa over the period 1970-2013. We employ the Gregory-Hansen (GH) method to test for the possibility of structural breaks in the money demand function. The Johansen Maximum likelihood procedure is carried out to determine the cointegration vector from which existence of one cointegrating vector is supported. Also based on the GH criterion, there is existence of one cointegrating vector. GH proposes three structural breaks for the money demand function. Results suggest that endogenous breaks occurred in 1991 and 1994. The GH cointegration equations reject M1 whilst M2 and M3 pass and we proceed to estimate the error-correction model. Complemented by the CUSUM and CUSUM of squares, the tests carried out suggest that monetary policy shifts did not introduce instability.